Data for Policy Initiative - Dabalen, Andrew (World Bank, Washington, DC, 2020)
The Data for Policy (D4P) initiative (D4P) is a new World Bank engagement to improve National Statistical Systems (NSS) by enhancing the availability, timeliness, quality, and relevance of key data for evidence-based decision making. Working at national and regional levels, the D4P ‘package’ includes production of a core set of economic, social, and sustainability statistics essential for monitoring and evaluating public policies and programs. Good quality, timely, and relevant statistics are crucial to monitor social and human development outcomes. They can also help identify what policies work, and which do not, in promoting inclusive growth and eradicating poverty. Having reliable, timely data is particularly important for poor countries to allow them to allocate limited resources most efficiently. At the same time, the World Bank’s support for countries’ statistical capacity has become even more critical as the world strives to achieve the Sustainable Development Goals (SDGs).